EVALUATION OF THE EFFICACY OF Brassica oleracea L. ALCOHOLIC EXTRACT ON THE LEVELS OF D3 AND ANTIOXIDANTS IN ALBINO MALE RATS DOSED WITH PARACETAMOL - RASOUL, WAFAA MOHAMMED RIDHA ABDEL; JWAD, SAHER MAHMOOD (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2022)
The Aim: The study included assessment of biochemical parameters such as levels of vitamin D3, reduced and oxidized glutathione, malondialdehyde and lipid peroxide. Place and Duration of Study: This study was carried out in the animal house of the Faculty of Education for Girls / University of Kufa, from 1/10/2021 to 1/12/2021. Study Design: as twenty-eight male albino rats of the Sprague Dawley strain were followed at the age of three months to evaluate the protective efficiency of the alcoholic extract of the Brassica oleracea flowers against paracetamol-induced hepatotoxicity and nephrotoxicity. Methodology: Rats' weights were between 216-246, divided into 4 groups in each group, 7 rats. The first group was dosed orally with tap water, which is the control group, and the second group was treated with paracetamol at a concentration of 2000 mg / kg orally, the third group was administrated with the alcoholic extract of Brassica oleracea flowers at a concentration of 500 mg/kg + paracetamol at a concentration of 2000 mg / kg orally as well, and with regard to the last group, only the alcoholic extract was given, where the dosing process lasted for 60 days ,once a day. Results : The study included assessment of biochemical parameters such as levels of vitamin D3, reduced and oxidized glutathione, malondialdehyde and lipid peroxide. The results of the statistical analysis recorded a significant (P<0.05) decrement in the levels of vitamin D3, reduced and oxidized glutathione, in contrast, a notable (P<0.05) increase in the levels of malondialdehyde and lipid peroxide in the group that was submitted to paracetamol when compared with the control group and the rest of the experimental groups. As for the group that was subjected to the extract only, it showed a significant (P<0.05) increment in the levels of vitamin D3, reduced and oxidized glutathione, and conversely a remarkable decrease (P<0.05) in the levels of malondialdehyde and lipid peroxide compared with the control group. Conclusion: The conclusion is that the alcoholic extract of Brassica oleracea flowers has shown a preventive activity against the pathological effects of paracetamol, possibly due to its chemical antioxidant contents.